The isolation, purification and partial, characterization of an alkaloid from the leaves of Salai Ziziphus talanai (Blanco) Merrill of the family Rhamnaceae. - Camus, Myra Manzano
A phytochemical screening conducted on the fresh of Ziziphus talanai(Blanco) Merrill of the family Rhamnaceae showed to be positive for alkaloids which was isolated, purified and subjected to an IR spectroscopic analysis. The findings showed one alkaloid with a melting point of 58.03 degrees centigrade to 159.1 degrees centigrade, an Rf value of 0.77 and a percentage of 0.0075. The results of the IR spectroscopic analysis showed an intramolecularly hydrogen bonded O-H stretch, C-H stretch, an N-H deformation, an N-H secondary deformation, an asymmetric bend and scissor, a gemdimethyl doublet, an aromatic amine and primary alcohol.